Cemento-ossifying fibroma - Rangila Ram; Anita Singhal; Parul Singhal (Wolters Kluwer Medknow Publications, 2012)
The cemento-ossifying fibroma is classified as a fibro-osseous lesion of the jaws. It commonly presents as a progressively growing lesion that can attain an enormous size with resultant deformity if left untreated. A case of cemento-ossifying fibroma involving the left mandible is described in a 35 year old female patient. The clinical, radiographic and histological features as well as surgical findings are presented. The cemento-ossifying fibroma is a central neoplasm of bone as well as the periodontium which has caused considerable controversy because of the confusion regarding terminology and the criteria for its diagnosis.